THE EFFECT OF THE QUANTUM LEARNING MODEL ASSISTED WITH VIDEO ON STUDENTS' COGNITIVE LEARNING OUTCOMES IN SMP NEGERI 5, KUPANG - Bendelina Dimu Ratu; Agus Maramba Meha; Thedora Sarlotha Nirmala Manu (Biotik, 2021)
This study aims to determine the effect of the video-assisted quantum learning model on the cognitive learning outcomes of students at SMP Negeri 5 Kupang City on the subject of Biology with the topic of additives and addictive substances. The research method used is quasi-experimental research, with a posttest-only control design. The research population was all students of class VIII with a total of 398 people, with the research sample consisting of 2 classes namely class VIII as the experimental class and class VIIIH as the control class totaling 30 students. Data collection techniques using learning outcomes tests with instruments in the form of multiple-choice questions and essays. Learning outcomes data were analyzed using SPPS version 22-assisted t-test. Based on the results of the hypothesis test, the t-count value was 8.424 with a significance of 0.000 <0.05, indicating a significant effect on the implementation of the quantum learning model on students' cognitive learning outcomes. In the quantum learning process, the learning atmosphere is comfortable and fun, students are actively involved during the learning process, with the help of video media aiming to sharpen students' memories of learning materials and make students enthusiastic about following lessons, as well as being responsible for completing tasks given by the teacher, dare to argue By making conclusions, the use of video media helps the learning process run smoothly to obtain satisfactory results. The results of the study can be concluded that there is a significant effect of the use of video-assisted quantum learning models on students' cognitive learning outcomes.